2009
DOI: 10.1111/j.1600-0714.2009.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

FGF‐2‐loaded collagen scaffolds attract cells and blood vessels in rat oral mucosa

Abstract: FGF-2-loaded scaffolds displayed a faster influx of host cells, an increased rate of vascularization, and a reduced differentiation of myofibroblasts. These scaffolds might therefore be highly suitable for intra-oral reconstructions, such as cleft palate repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…In the bone‐forming test, histological samples obtained 35 d after implantation of the FGF‐2‐loaded scaffold frequently showed an increase in giant cells around the scaffold, suggesting active wound healing and remodeling. A previous study also revealed giant cells in FGF‐2‐loaded collagen scaffold after implantation in rat oral mucosa . It has been demonstrated that β‐TCP degradation promotes an osteogenic marker of osteoblastic cells, alkaline phosphatase activity, resulting from calcium ion release .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the bone‐forming test, histological samples obtained 35 d after implantation of the FGF‐2‐loaded scaffold frequently showed an increase in giant cells around the scaffold, suggesting active wound healing and remodeling. A previous study also revealed giant cells in FGF‐2‐loaded collagen scaffold after implantation in rat oral mucosa . It has been demonstrated that β‐TCP degradation promotes an osteogenic marker of osteoblastic cells, alkaline phosphatase activity, resulting from calcium ion release .…”
Section: Discussionmentioning
confidence: 82%
“…Regenerative scaffolds should induce rapid reconstructive tissue ingrowth through wound healing. Up‐regulation of the ingrowth of regenerative tissue and blood vessels into the scaffold is generally relevant to the morphology of the scaffold . When clinically applied as a bone‐graft material, β‐TCP controls pore characteristics such as pore volume fraction, size and structure.…”
mentioning
confidence: 99%
“…Jansen et al implanted FGF‐2 loaded collagen scaffolds in the palate of rats, which led to an increased number of host cells and a higher vascularization rate. Furthermore, there was a reduced number of myofibroblasts, decreasing the wound contraction, one of the major problems of palate wound healing.…”
Section: Fgf‐2/fgfr‐1 Expression In Normal Oral Mucosa and During Oramentioning
confidence: 99%
“…Basic fibroblast growth factor (bFGF), a member of fibroblast growth factor family, has various biological functions both in bone regeneration and angiogenesis. [19,[22][23][24] Expressed in osteoblasts and stored in extracellular matrix, [25] bFGF plays a vital role in mitogenesis, cellular migration, and differentiation. Several studies suggested that bFGF is essential for normal development and formation of bone, tendons, and ligaments in the skeleton.…”
Section: Introductionmentioning
confidence: 99%